Thermally grown ZnO nanorods from Zn ingot - Han, KR; Jang, HJ; Kim, CS (CERAMIC SOC JAPAN-NIPPON SERAMIKKUSU KYOKAI, 2005)
ZnO rods were synthesized from Zn ingot under various pressures of mixed gas of Ar/O-2(90/10 mass%) from 60 to 95 kPa. ZnO rods were grown on both the surface of the Zn ingot and the vertically mounted quartz substrate. ZnO dots were at first developed on the grain boundaries of the Zn ingot and continued to grow as rods. ZnO rods were also developed on the quartz substrate with a thickness similar to 1.5 times those of rods grown on the ingots. ZnO nanorods of similar to 100 nm in diameter were vertically grown with good uniformity on the quartz substrate.
Keywords: CHEMICAL-VAPOR-DEPOSITION; ZINC-OXIDE NANOWIRES; CATALYTIC GROWTH; NANOSTRUCTURES